(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Trelew (1997) of the Argentine writer Marcelo Eckhardt is composed by essays, stories and a novel that they develop in an inserted way. Characterized by the generic mixture, and by a insistent description of the geographic and cultural space of the Patagonia, Trelew develops the mitografìa of the city homonym simultaneously that constructs that of the own author who expands and diversifies his speech in other voices, turning the text in a plural text by the forms and by the voices that form it.